PERAN MASYARAKAT NELAYAN DALAM PENINGKATAN EKONOMI DI DESA PEMATANG CENGAL TIMUR KECAMATAN TANJUNG PURA - Muhammad sholihin; Hj. Kamaliah R; Anjur Perkasa Alam (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
To find out the obstacles faced by fishermen in increasing their income in Pematang Cengal Timur Village, Tanjung Pura District. This study aims to determine the role of the fishing community in improving the economy in Pematang Cengal Timur Village, Tanjung Pura District. To obtain the data needed in this study, field research was used, namely by using data collection tools through observation, interviews or structured interviews, and documentation. The data obtained were then processed and analyzed. In this study, qualitative research was used with a descriptive analysis approach, namely by describing the research results obtained through structured interviews with research sources. The government's role in empowering fishing communities in Pematang Cengal Tanjung Pura Village has been able to carry out its role effectively. through programs that the Government has provided to fishing communities such as education and training, counseling and assistance, and fishermen's institutions as well as providing convenience for fishermen in running their businesses such as providing attention and support as well as in order to improve the welfare of the fishing community. Efforts to empower the fishing community to improve the economy in Pematang Cengal Tanjung Pura Village in improving the community's economy have increased due to the efforts to empower the fishing community given the command, the income of the community in Pematang Cengal Tanjung Pura Pantai Village has increased because the government has provided assistance in the form of fisherman cards, providing facilities and infrastructure as well as providing business capital funds to fishermen, with this assistance the fishing community in Pematang Cengal Tanjung Pura Village is greatly helped and the economic improvement of the Pematang Cengal Tanjung Pura Pantai community can increase from the year before the empowerment.